A newly developed algorithm for switching outpatient medications to medications listed in the hospital formulary: a prospective real-word evaluation in patients admitted electively to hospital - Finja Möller; Malte Oetting; Andreas Spiegel; Olaf Zube; Thilo Bertsche (European Journal of Clinical Pharmacology, 2024)
Purpose In many countries, outpatient and inpatient care are separated. During hospitalization, therefore, switching the outpatient medication to medication of the hospital formulary is required. Methods We newly designed a switching algorithm in six switching steps (S0–S5) and conducted a study at Bundeswehr Hospital Hamburg (300 beds, 80% civilians). We performed (i) a medication reconciliation to obtain information on outpatient medications and (ii) a medication review to solve drug-related-problems, e.g., drug-drug interactions. We applied (iii) the algorithm to switch medications to the hospital formulary. Results (i) We identified 475 outpatient medications (median per patient: 4; Q25/Q75 2/7) in 100 patients consecutively admitted to hospital (median age: 71; Q25/Q75: 64/80 years). Of 475 medications, the switching algorithm could not be used since product names were missing in 23.9% and strength in 1.7%. In 3.2%, switching was not required since medication was not prescribed during the hospital stay. (ii) Drug-drug interactions were identified in 31 of 79 patients with more than one medication. (iii) Of 475 medications, 18.5% were on the hospital formulary and therefore did not need to be switched (S0), 0.2% were on a substitution-exclusion list not allowing switching (S1), 42.0% were switched to a generic medication of the hospital formulary (S2), 1.7% to a therapeutically equivalent medication (S3), 0.4% were patient-individually switched (S4), and for 8.2% a standardized/patient-individual switching was not possible (S5). Conclusions Despite comprehensive medication reconciliation, patient- and medication-related information for switching medications to the hospital formulary was often missing. Once all the necessary information was available, standardized switching could be easily carried out according to a newly developed switching algorithm.

Avoiding incompatible drug pairs in central-venous catheters of patients receiving critical care: an algorithm-based analysis and a staff survey - Leonhardt Alexander Fabian Wagner; Martina Patrizia Neininger; Jan Hensen; Olaf Zube; Thilo Bertsche (European Journal of Clinical Pharmacology, 2023)
Purpose In a critical care setting, we aimed to identify and solve physico-chemical drug incompatibilities in central-venous catheters considering the staffs’ knowledge and assumptions about incompatibilities. Methods (i) After positive ethical vote, an algorithm to identify incompatibilities was developed and applied. The algorithm was based on KIK ® database and Stabilis ® database, the drug label, and Trissel textbook. (ii) A questionnaire was created and used that asked staff for knowledge and assumptions about incompatibilities. (iii) A 4-step avoidance recommendation was developed and applied. Results (i) At least one incompatibility was identified in 64 (61.4%) of 104 enrolled patients. Eighty one (62.3%) of 130 incompatible combinations affected piperacillin/tazobactam and in 18 (13.8%) each furosemide and pantoprazole. (ii) 37.8% ( n = 14) of the staff members participated in the questionnaire survey (median age: 31, IQR: 4.75 years). The combination of piperacillin/tazobactam and pantoprazole was incorrectly judged to be compatible by 85.7%. Only rarely felt the majority of respondents unsafe in administering drugs (median score: 1; 0, never to 5, always). (iii) In those 64 patients with at least one incompatibility, 68 avoidance recommendations were given, and all were fully accepted. In 44 (64.7%) of 68 recommendations “Step 1: Administer sequentially” was suggested as a avoidance strategy. In 9/68 (13.2%) “Step 2: Use another lumen”, in 7/68 (10.3%) “Step 3: Take a break”, and in 8/68 (11.8%) “Step 4: Use catheters with more lumens” were recommended. Conclusions Although incompatibilities were common, the staff rarely felt unsafe when administering drugs. Knowledge deficits correlated well with the incompatibilities identified. All recommendations were fully accepted.

Intake of aspirin prior to metamizole does not completely prevent high on treatment platelet reactivity - Christian Pfrepper; Carolin Dietze; Yvonne Remane; Thilo Bertsche; Susanne Schiek; Thorsten Kaiser; Ines Gockel; Christoph Josten; Sirak Petros (European Journal of Clinical Pharmacology, 2020)

Fall-risk-increasing adverse reactions—is there value in easily accessible drug information? A case-control study - Susanne Schiek; Katja Hildebrandt; Olaf Zube; Thilo Bertsche (European Journal of Clinical Pharmacology, 2019)

Successful strategy to improve the specificity of electronic statin–drug interaction alerts - Hanna Marita Seidling; Caroline Henrike Storch; Thilo Bertsche; Christian Senger; Jens Kaltschmidt; Ingeborg Walter-Sack; Walter Emil Haefeli (European Journal of Clinical Pharmacology, 2009)

Pro-active provision of drug information as a technique to address overdosing in intensive-care patients with renal insufficiency - Thilo Bertsche; Martina Fleischer; Johannes Pfaff; Jens Encke; David Czock; Walter E. Haefeli (European Journal of Clinical Pharmacology, 2009)

Rule-based standardised switching of drugs at the interface between primary and tertiary care - Stefanie U. Walk; Thilo Bertsche; Jens Kaltschmidt; Markus G. Pruszydlo; Torsten Hoppe-Tichy; Ingeborg Walter-Sack I; Walter E. Haefeli (European Journal of Clinical Pharmacology, 2008)